2022
DOI: 10.3390/en15114155
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Resource Consumption Accounting in Achieving Competitive Prices and Sustainable Profitability

Abstract: This study examines the roles of resource consumption accounting and competitive prices in attaining sustainable profitability. The objectives were (1) to determine whether the adoption of resource consumption accounting practices yields significant improvements in competitive strategies in a highly competitive situation where activity-based costing has proved to be insignificant, and (2) to ascertain if the positive relationship between competitive pricing and sustainable profitability is increased by the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The main limitation of current paper was time, cost, and not available some related source (Mustafa et al, 2022). Finally, the study reached a number of results based on the aforesaid studies, the most important of which is found that adherence to international standards and accounting conservatism contribute to increasing the quality and continuity of profits and the ability of shareholders to forecast future cash flows on the one hand and increase the level of relevance, reliability and quality of financial information by reducing information asymmetry and on the other hand, as well as increasing investments in the company to match the information provided to investors (Jaf et al, 2019 andRashid, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of current paper was time, cost, and not available some related source (Mustafa et al, 2022). Finally, the study reached a number of results based on the aforesaid studies, the most important of which is found that adherence to international standards and accounting conservatism contribute to increasing the quality and continuity of profits and the ability of shareholders to forecast future cash flows on the one hand and increase the level of relevance, reliability and quality of financial information by reducing information asymmetry and on the other hand, as well as increasing investments in the company to match the information provided to investors (Jaf et al, 2019 andRashid, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is impossible to say that a concept is rejected or accepted based on its ability and necessity for objective measurement. The figure shows the defined procedures, because these attributes will change with the development of scientific research and find measurement methods and modern measurement methods and reasonable degree of objectivity (Mustafa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A small shift was made when activity-based costs (ABC) were introduced (Sabir et al, 2011). This represented certain advancement, as costs per individual activity could be controlled in a better way and provided some sort of connection with the whole (Mustafa et al, 2022). Regardless of this, the measuring system based on cost accounting has proved totally inadequate for contemporary circumstances.…”
Section: Financial Performancementioning
confidence: 99%